Origin of the fluorescence in silica-based nanoparticles synthesized from aminosilane coupling agents - Saita, Satoshi; Kawasaki, Hideya (Journal of luminescence, 2021)
Fluorescent silicon/silica-based nanoparticles (NPs) that are synthesized from aminosilane coupling agents in the presence of reducing agents (e.g., citric acid) have been extensively investigated for applications as bioimaging agents, sensing materials, and visible-light-emitting materials due to their low cost, low toxicity, high water stability, and high photostability. However, the origin of the fluorescence of these NPs remained unknown. This study demonstrated the synthesis of fluorescent silica-based NPs from 3-(aminopropyl) triethoxysilane (APTES) in the presence of ascorbic acid at 80 °C and 230 °C; furthermore, the origin of the fluorescence of the synthesized NPs was investigated. The hydrothermal synthesis at 230 °C yielded highly fluorescent silica-based NPs with a quantum yield (QY) of 32.3%. However, the NPs that were synthesized at 80 °C exhibited a low QY of ~2.0%. The analysis of the characteristic absorption bands and the emission spectra of the NPs indicated that the fluorescence originated from the surface defect pairs (dioxasilyrane (=Si(O2)) and silylene (Si)) in silica. The hydrothermal treatment of the silica-based NPs increased the number of surface defect pairs and suppressed the non-emissive thermal decay in the NPs. This resulted in the formation of highly fluorescent silica-based NPs. [Display omitted] •Fluorescent silica NPs (F–SiO2 NPs) were synthesized from APTES with AA as a reducing agent.•F–SiO2 NPs were prepared by hydrothermal treatment at 80 °C and 230 °C.•The origin of fluorescence of NPs was defect pairs, i.e., dioxasilyrane and silylene.•Hydrothermal treatment increased the number of surface defect pairs in F–SiO2 NPs.•F–SiO2 NPs at 230 °C were highly photoluminescent with a quantum yield of 32.3%.